THE EFFECTS OF HUMAN CAPITAL, EMPLOYMENT, AND DEMOGRAPHY ON POVERTY REDUCTION (RURAL AND URBAN AREAS IN INDONESIA) (International Journal of Psychosocial Rehabilitation, 2020)
In SDGs, the top priority is no poverty. The problem of poverty must be understood as a global problem so that the handling must be done in a global context as well, especially for a developing country, including Indonesia. This study aims to determine the effect of human capital, employment, and demography on poverty reduction (rural and urban areas in Indonesia). This research used multiple linear regression and independent t-test analytical tools. The results show that in rural areas, education has a negative and significant effect on poverty, health has a negative but not significant effect on poverty, gender has a negative and significant effect on poverty, and employment has a positive but not significant effect on poverty. In urban areas, education has a negative and significant effect on poverty, employment has a positive but not significant effect on poverty, and gender has a negative and significant effect on poverty. The results of the comparative test show there are significant differences between urban and rural poverty levels.